Sintesis Dan Karakterisasi Karbon Aktif Doping TiO2 Untuk Menurunkan Kadar Asam Lemak Bebas Pada Minyak Jelantah - Cen Rahman; Mulda Muldarisnur (Jurnal Fisika Unand, 2024)
Research has been conducted on reducing the levels of free fatty acids in used cooking oil using activated carbon derived from teak sawdust doped with TiO2. The used cooking oil employed in this study underwent five frying cycles. The activated carbon was derived from teak sawdust and activated using a 10% ZnCl2 solution. The activated carbon was tested for moisture and ash content. The activated carbon was doped with TiO2 in various mass ratios, specifically 3:100, 6:100, 9:100, and 12:100, using solid-state synthesis at a temperature of 500 Â°C. The doped carbon was subjected to XRD analysis. The purified used cooking oil was tested for free fatty acid levels and clarity using UV-vis spectroscopy. The moisture content of the activated carbon was found to be 3.60%, while the ash content was 1.95%. XRD analysis revealed that the crystal size of the activated carbon was 38.9 nm, which decreased to 27.2 nm after TiO2 doping. Free fatty acid levels decreased from 1.18% to 0.29% in the free fatty acid content test. In the UV-vis measurement, the absorbance value for used cooking oil was higher at 4.5734, while purified oil had an absorbance value of 4.1985. The research results indicated that the best mass ratio of activated carbon to TiO2 was 9:100. The use of TiO2 doped activated carbon as an adsorbent effectively reduced the levels of free fatty acids in used cooking oil.